Poverty alleviation in Jordan : lessons for the future - Shaʻbān, Raḍwān ʻAlī (Orientations in development., 2001)
"The incidence of poverty in Jordan declined between 1992 and 1997. This decline is related to the change in government policies from generalized food subsides, benefiting the rich more than the poor, to targeted cash assistance for the poor. Yet poverty reduction remains a major policy challenge for the country since the improvement was driven by reduced inequality and not by positive economic growth. The sustainability of Jordan's social safety net is limited by the growth of the budget and the economy. The report therefore examines Jordan's recent experience in poverty alleviation schemes to draw lessons for future policy design improvements. The report concludes that resumption and sustainability of growth, as well as continued prioritization of human development policies, remain the bulwark of sustained poverty alleviation for Jordan in the future.